On Commitments - Jennifer W. Reynolds (Washington University Journal of Law & Policy, 2012)
In standard interest-based negotiations or mediations, commitments are the final stage of a process in which negotiators manage both substantive issues and relational concerns while intentionally dismantling unproductive positions so that the parties may explore the integrative potential of identifying underlying interests, and then generating value-creating options to satisfy those interests. Put another way, interest-based processes transform some number of party interests into action items, deliverables, contract provisions, memorandums of understanding, preambles, press releases, promises, declarations of intention; that is, interests become commitments. And often the opposite is true: commitments can become interests, insofar as they are constitutive elements (explicit or not) in future negotiations and decisions.
Keywords: Legal profession; Lawyering; Dispute systems design (DSD); Alternative dispute resolution (ADR); Interests; Interest-based negotiation; Institutions; Human behavior; Psychology; Why Good Companies Go Bad (book); Donald Sull; Case studies